Strengthening of Reinforced Concrete Columns Using Composite of Near Surface Mounted CFRP Strips and Fabric - Abokwiek, Raed (2016)
A Master of Science thesis in Civil Engineering by Raed Abokwiek entitled, "Strengthening of Reinforced Concrete Columns Using Composite of Near Surface Mounted CFRP Strips and Fabric," submitted in January 2016. Thesis advisor is Dr. Jamal A. Abdalla, thesis co-advisors are Dr. Rami A. Hawileh and Dr. Tamer El Maaddawy. Soft and hard copy available.